Association Between Atopic Keratoconjunctivitis and the Risk of Recurrent Corneal Erosion - Jan, Ren-Long; Weng, Shih-Feng; Wang, Jhi-Joung; Tseng, Sung-Huei; Chang, Yuh-Shin (Frontiers in Medicine, 2021)
Abstract Purpose: To investigate the risk of recurrent corneal erosion (RCE) in patients with atopic keratoconjunctivitis (AKC). Methods: This nationwide, retrospective, population-based, matched-cohort study included 184,166 newly diagnosed patients with AKC, selected from the Taiwan National Health Insurance Research Database, and identified by the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 372.05. The age-, sex-, and potential comorbidities-matched control group included 184,166 patients without AKC selected from the Taiwan Longitudinal Health Insurance Database, 2000. Patient information was collected between 1 January 2004 and 31 December 2011, and both groups of patients were tracked from the index date until December 2013. The incidence and risk of RCE (ICD-9-CM code 361.42) was compared between the groups. The adjusted hazard ratio (HR) for RCE was obtained by a Cox proportional hazard regression analysis. The Kaplan–Meier analysis was performed to calculate the cumulative incidence of RCE. Results: In total, 564 patients with AKC and 406 controls developed RCE during the follow-up period. The incidence of RCE was 1.45 times higher in patients with AKC than in controls (95% confidence interval [CI] = 1.27–1.64; P < 0.0001). After adjusting for potential confounders, including diabetes mellitus, keratoconjunctivitis sicca, corneal transplantation, ocular blunt trauma, corneal dystrophy, and band keratopathy, patients with AKC were 1.36 times more likely to develop RCE than controls (adjusted HR, 1.36; 95% CI = 1.19–1.54; p < 0.05). Conclusions: Patients with AKC had an increased risk of developing RCE and should be informed of this risk.